PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP AKTIVITAS DAN HASIL BELAJAR KIMIA SISWA KELAS XI IPA SMA NEGERI 8 MEDAN T.P 2024/2025 - Feriaman; Ajat Sudrajat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to determine the influence of the Problem BasedLearning (PBL) learning model on the activities and learning outcomes of studentsin grade XI of Science at SMA Negeri 8 Medan T.P 2024/2025 on colloid systemmaterials. The sample of this study is 36 students in class XI-8 as an experimentalclass using the Problem Based Learning learning model and 30 students in classXI-2 as a control class using the conventional model. Data collection techniques arecarried out through observation, objective tests, and documentation. The researchdesign used was Two Groups (Pretest and Posttest). The results of the study showthat there is a positive and significant influence of the Problem Based Learninglearning model on the activities and learning outcomes of chemistry students ingrade XI Science of SMA Negeri 8 Medan T.P 2024/2025. This can be seen fromthe average value of activities and learning outcomes of the experimental class,which is 82.29 and 81.67, while the average activity and learning outcomes of thecontrol class are 74.17 and 79.17. 2. Then, tcalculated for the learning activities of theexperimental class is 11,262 > ttable, which is 1.6696. Likewise, for the learningoutcomes of the experimental class, the calculation is 3,439 > ttable, which is 1,669.